(3dG JNHQj GdQLd Hcd TFs - (3YdGA GdOjf, CSeGAs; (3aQjO, VjGAs; (3efJUQ, ESdGes ((3GdbGgQIs (3GdQhGb ddfTQ hGdJhRjYs, 2023)
(3cJH cJjQ GJcdeJ Yf GdYdGbGJ hGdJYGaj hGdbhI GdCfKhjI, dcf GdaQb gfG Efj HUQGMI hUOb hLQCI gbhdc Gddj GdQLGdI YeQgG eGgJacQ Jbhdg, hGddj GdSJGJ NGjaI JSeYg(B! (3McTadc cd Gddj eG JYQaghT Yf NHGjG GdYdGbI Hjf GdQGLd hGdSJ, hMYdec GRGj JJYGedj UM eY GdQGLd, GRGj JcSHjg heG JbYjT aj GdCNWGA Gddj hbYJ ajgG bHdc edGjjf GdSJGJs
Keywords: (3GdYdGbGJ GdGSQjIs; (3GdeTGcd GdGLJeGYjIs; (3GdfLGM GdTNUjs